Hidden transcripts of the gig economy: labour agency and the new art of resistance among African gig workers. (October 2020) - Anwar, Mohammad Amir; Graham, Mark
In this article, we examine how remote gig workers in Africa exercise agency to earn and sustain their livelihoods in the gig economy. In addition to the rewards reaped by gig workers, they also face significant risks, such as precarious working conditions and algorithmic workplace monitoring, thus constraining workers' autonomy and bargaining power. Gig workers, as a result, are expected to have fewer opportunities to exert their agency – particularly so for workers in Africa, where the high proportion of informal economy and a lack of employment opportunities in local labour markets already constrain workers' ability to earn livelihoods. Instead, we demonstrate how remote workers in Africa manage various constraints on one of the world's biggest gig economy platforms through their diverse everyday resilience, reworking and resistance practices (afterKatz, 2004 ). Drawing from a rich labour geography tradition, which considers workers to 'actively produce economic spaces and scales', our main theoretical contribution is to offer a reformulation of Katz's notions of 'resistance', 'resilience' and 'reworking' as everyday practices of gig workers best understood as 'hidden transcripts' of the gig economy (Scott, 1990 ). The article draws on in-depth interviews (N=65) conducted with remote workers during the fieldwork in five selected African countries.